Pengaruh Media Sosial Terhadap Pembentukan Identitas Diri Remaja kelurahan Kelapa Lima RT 36/ RW16 Kecamatan Kelapa Lima Kota Kupang - Ndueng, Yovita; Pareira, Mariana Ikun RD; Makleat, Nirwaning (Education For All, 2025)
ABSTRACTSocial media has become a widely used platform among adolescents, including inthe formation of self-identity. Social media is not only a means of communication but alsoa space for expression where adolescents can create, explore, and reinforce their selfimage. In this process, social media allows adolescents to utilize various features such asphoto uploads, videos, and statuses that reflect their personality. This study aims to analyzethe influence of social media usage on the self-identity formation of adolescents inRT18/RW1, Kelapa Subdistrict, using a narrative qualitative approach. The researchsubjects consist of adolescents aged 18–19 years.The findings of the study indicate that social media has both positive and negativeinfluences on the self-identity formation of adolescents. On the positive side, social mediaenables adolescents to expand their social networks and gain emotional support fromcommunities, such as peers, who provide positive feedback. This helps enhance their selfconfidence and self-satisfaction. However, on the negative side, uncontrolled use of socialmedia can lead to excessive social comparisons, increase anxiety, and disrupt theconsistency of self-identity. These findings also highlight the importance of the role offamily and the social environment in managing the negative impacts of social media onadolescents and providing guidance for the wise use of social media.